PENYELESAIAN SENGKETA PEMBAGIAN HARTA WARISAN OLEH KEPALA DESA SEBAGAI HAKIM PERDAMAIAN DESA - Hentika Ruhmana; AD Basniwati (Private Law, 2023)
This study aims to determine the implementation of inheritance dispute resolution by the village head as a village peace judge and to find out the inhibiting and supporting factors of inheritance dispute resolution by the village head as a village peace judge. This research was applying empirical legal research methods using a Conceptual Approach, Statutory Approach, Sociological Approach, and Case Approach. The research results revealed that the disputes were resolved using non-litigation settlements and using the Islamic legal system (Fara'id). The inhibiting factor for resolving inheritance disputes was the reluctance of the parties to come to the village office. Moreover, the parties did not provide proof marks. In some cases, there were parties who did not respect the rights of others. The supporting factors for inheritance dispute resolution are the will of the parties to resolve their dispute, the truthfulness of the parties, and the mediator has good ethics.